Indexing Reservoir Channel Catfish Population Density and Size Structure with Tandem, Baited Hoop Nets. (3rd May 2021) - Tyszko, Stephen M.; Pritt, Jeremy J.; Conroy, Joseph D.
Abstract: Fisheries managers efficiently sample reservoir Channel Catfish Ictalurus punctatus populations with tandem, baited hoop nets. However, catchability (the fraction of a fish stock caught with a defined unit of effort) of Channel Catfish with this gear and the size selectivity of this gear are not fully known. Furthermore, scientists have not identified a standard sampling period that maximizes catches while minimizing variation in catchability. Here, we estimated Channel Catfish population density (number/ha) and catchability with tandem, baited hoop nets using mark–recapture methods in three Ohio reservoirs during May–July 2016–2018. We tested for differences in catchability (1) among reservoirs; (2) among 50‐mm length categories; and (3) by week. We then tested CPUE as an index of density by simulating the sampling of populations with different densities based on observed variation in catchability and estimating the statistical power to detect density differences. We found that total catchability differed among study reservoirs, among length categories, and among sampling events but did not consistently change during the May–July sampling period. Catchability of 50‐mm length categories did not differ among reservoirs. The greatest catchability was observed for 400–649‐mm Channel Catfish. Our power analysis showed that we could detect a large (>2:1 effect sizes) difference in density with 80% power by using 20 or more sample sites. Furthermore, our length‐category‐specific catchability estimates provide information to reduce bias in size structure, growth, and mortality estimates derived from Channel Catfish samples collected with tandem, baited hoop nets. We encourage further development, validation, and application of tandem, baited hoop nets to better understand differences in reservoir Channel Catfish densities and size structures.